2015
DOI: 10.1016/j.cj.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of copper tolerance of Arabidopsis by transgenic expression of an allene oxide cyclase gene, GhAOC1, in upland cotton (Gossypium hirsutum L.)

Abstract: Allene oxide cyclase (AOC, E 5.3.99.6) is an essential enzyme in the jasmonic acid (JA) biosynthetic pathway and mediates a wide range of adaptive responses. In this report, five AOC genes (GhAOC1-GhAOC5) were cloned from upland cotton (Gossypium hirsutum L.), sequenced, and characterized. Real-time PCR analysis indicated that the transcripts of GhAOCs were abundantly expressed in roots and less in fibers, and regulated in cotton plants under methyl jasmonate (MeJA) and CuCl 2 stresses. To investigate the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…To characterize ClAOC1 and ClAOC2, a multiple sequence alignment was performed for their full-length amino acid sequences, as well as other published AOC proteins, such as SlAOC from Solanum lycopersicum [6], HvAOC from Hordeum vulgare [13], HnAOC from Hyoscyamus niger [31], JcAOC from Jatropha curcas [32], AaAOC from Artemisia annua [33], OsAOC from Oryza sativa [12], LmAOC from Leymus mollis [34], TaAOC1 from Triticum aestivum [17], GhAOC1 from Gossypium hirsutum [8], GmAOC3 from Glycine max [18], CsAOC from Camellia sinensis [35], and Ljaoc1 from Lotus japonicus [10]. The results showed that the identity between ClAOC1 and ClAOC2 was 62.13%, and the amino acid sequences of ClAOC1 and ClAOC2 shared 58.05% to 69.08% identity with other AOC proteins ( Figure 2).…”
Section: Characterization Of Claoc1 and Claoc2mentioning
confidence: 99%
See 2 more Smart Citations
“…To characterize ClAOC1 and ClAOC2, a multiple sequence alignment was performed for their full-length amino acid sequences, as well as other published AOC proteins, such as SlAOC from Solanum lycopersicum [6], HvAOC from Hordeum vulgare [13], HnAOC from Hyoscyamus niger [31], JcAOC from Jatropha curcas [32], AaAOC from Artemisia annua [33], OsAOC from Oryza sativa [12], LmAOC from Leymus mollis [34], TaAOC1 from Triticum aestivum [17], GhAOC1 from Gossypium hirsutum [8], GmAOC3 from Glycine max [18], CsAOC from Camellia sinensis [35], and Ljaoc1 from Lotus japonicus [10]. The results showed that the identity between ClAOC1 and ClAOC2 was 62.13%, and the amino acid sequences of ClAOC1 and ClAOC2 shared 58.05% to 69.08% identity with other AOC proteins ( Figure 2).…”
Section: Characterization Of Claoc1 and Claoc2mentioning
confidence: 99%
“…Previous studies have revealed that the expression of AOC genes could be induced by treatments of different hormones, such as JA and SA [8,35,37]. To determine whether ClAOC1 and ClAOC2 are responsive to hormones, their expression patterns under treatments of different hormones (JA, SA, and ET) were examined by qRT-PCR.…”
Section: Expression Patterns Of Claoc1 and Claoc2 In Response To Hormmentioning
confidence: 99%
See 1 more Smart Citation
“…In another research, GhAOC1 overexpression in Arabidopsis plants under copper stress increased their photosynthetic efficiency, survival rate, and fresh and dry weight of the stem (compared to control) and reduced the damage to the cell membrane and lipid peroxidation. The Real-time PCR analysis showed that in linseed, GhAOC transcripts are widely expressed in roots and regulated under MeJAand CuCl2 stress (Wang et al, 2015). Research's has shown that MeJA synthesis is triggered through positive feedback, as genes that encode jasmonate synthesis are JA-inducible and jasmonate increases their expression.…”
Section: Molecular Assaymentioning
confidence: 99%
“…It reported that AOC gene expression is also associated with improved copper tolerance in cotton. In Arabidopsis plants, GhAOC1 overexpression has been found to be associated with higher survival rate, higher fresh and dry weight of the shoot, improved photosynthetic efficiency and reduced cell membrane damage and lipid peroxidation under copper-induced stress (Wang et al, 2015). In two species of transgenic wheat and Arabidopsis, the TaAOC1 gene has been found to be associated with increased salinity tolerance and jasmonate accumulation (Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%